Changes in inflammatory biomarkers in the nasal mucosal secretion after septoplasty - Marn Joon Park; Yong Ju Jang (Scientific Reports, 2022)
Abstract Deviated nasal septum (DNS) is suggested to be associated with nonspecific inflammation of the nasal mucosa. The authors hypothesized septoplasty may reduce nasal mucosal inflammation, therefore the authors aimed to measure various inflammatory biomarkers in the nasal secretion following septoplasty. Prospectively, 17 patients undergoing elective septoplasty were included. Symptomatic changes after septoplasty were evaluated with Sino-nasal Outcome Test (SNOT-22) and Nasal obstruction symptom evaluation (NOSE) scores. Using acoustic rhinometry, changes of the nasal airway volume were measured. Nasal secretion was collected within 2 weeks and 3 months before and after septoplasty, respectively. The inflammatory biomarker high-mobility group box 1 (HMGB1) and vasoactive intestinal peptide (VIP), and inflammatory cytokines including tumor necrosis factor α (TNF α), interferon γ (IFN-γ), interleukin-4 (IL-4), eotaxin-1, and regulated upon activation, normal T cell expressed and presumably secreted (RANTES) were quantified in the nasal secretion by enzyme-linked immunosorbent assays or multiplex bead array assays. The patients' mean age was 30.5 ± 6.8 (ranging from 19 to 43), consisting of 15 male and 2 female patients. The median SNOT-22 and NOSE scores changed from 54 to 14 and 78 to 15, respectively, both showing a significant decrease. In acoustic rhinometry, nasal cavity volume of convex side significantly increased after septoplasty, whereas significant discrepancy of nasal airway volume between concave and convex sides became insignificant. No significant difference was noted both before and after septoplasty between the concave and convex sides in all seven biomarkers. The HMGB1, RANTES, IL-4, and TNF-α concentrations following septoplasty showed significant decrease in 34 nasal cavities of 17 patients (all p < 0.05). However, when the 17 concave and 17 convex sides were analyzed separately, the significant reduction in four biomarkers were only significant in the concave sides (all p < 0.05), but not significantly reduced in convex sides. Septoplasty may have benefited not only in normalizing the nasal airflow and symptom improvement, but also in nonspecific inflammation attenuation in the nasal airway.